1982
DOI: 10.1128/jvi.43.1.174-181.1982
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DNA of a Nonoccluded Baculovirus, Hz-1V

Abstract: The DNA of the nonoccluded baculovirus (Hz-lV) obtained from the IMC-Hz-1 cell line was characterized by physicochemical and restriction endonuclease techniques. Hz-1V DNA isolated from purified virus had buoyant densities of 1.58 and 1.54 g/ml in CsCI-ethidium bromide density gradients, which corresponded to supercoiled and to relaxed circular and linear DNA, respectively. Neutral CsCl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Hz-1 virus was identified by Granados and coworkers in 1978 (22) as a persistent infecting baculovirus agent in the IMC-Hz-1 ovarian cell line. It is an enveloped, nonoccluded, rod-shaped virus that contains a double-stranded circular 228-kb DNA genome (12,24). The virus particles are usually heterogeneous in length according to examination by electron microscopy.…”
mentioning
confidence: 99%
“…Hz-1 virus was identified by Granados and coworkers in 1978 (22) as a persistent infecting baculovirus agent in the IMC-Hz-1 ovarian cell line. It is an enveloped, nonoccluded, rod-shaped virus that contains a double-stranded circular 228-kb DNA genome (12,24). The virus particles are usually heterogeneous in length according to examination by electron microscopy.…”
mentioning
confidence: 99%
“…It was isolated from persistently infected IMC-Hz-1 tissue culture cells by Granados and coworkers (9). The Hz-1 viral genome is a 228-kb covalently closed circular double-stranded DNA molecus (5,6,10). This virus can establish both persistent and productive infections in several lepidopteran insect cell lines.…”
mentioning
confidence: 99%
“…Defective virus particles containing genomic deletions have been observed in some Hz-1 viral isolates (5,6,10). Burand et al (5) showed that defective virus particles are generated following serial passage of the standard virus in vitro and are required for establishment of persistent infections.…”
mentioning
confidence: 99%
“…Hz-1 virus is rod-shaped, enveloped but with no occlusion body and its particle size is 414 ± 30 × 80 ± 30 nm (Burand et al , 1986). The viral genome of Hz-1 is 228 kb double-stranded circular DNA with a molecular weight of 1.31 × 10 7 Da (Huang et al , 1982). Hz-1 virus was previously classified as a member of Baculoviridae , and defined as the type species of the Nudibaculovirinae .…”
Section: Introductionmentioning
confidence: 99%
“…, 1986). The viral genome of Hz‐1 is 228 kb double‐stranded circular DNA with a molecular weight of 1.31 × 10 7 Da (Huang et al. , 1982).…”
Section: Introductionmentioning
confidence: 99%